2021
DOI: 10.3389/fpls.2020.564802
|View full text |Cite
|
Sign up to set email alerts
|

Bumblebee Behavior on Flowers, but Not Initial Attraction, Is Altered by Short-Term Drought Stress

Abstract: Climate change is leading to increasing drought and higher temperatures, both of which reduce soil water levels and consequently water availability for plants. This reduction often induces physiological stress in plants, which in turn can affect floral development and production inducing phenotypic alterations in flowers. Because flower visitors notice and respond to small differences in floral phenotypes, changes in trait expression can alter trait-mediated flower visitor behavior. Temperature is also known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 71 publications
(53 reference statements)
2
20
0
1
Order By: Relevance
“…Finally, in addition to visitation rates, changes due to reduced water availability might also affect pollinator behavior on flowers (Höfer et al, 2021). Behavioral changes, such as increasing handling time, can impact pollen transfer to the stigma and pollen removal and can be better proxies for pollination efficiency than visitation rates (Willcox et al, 2017;Willmer et al, 2017).…”
Section: Caveats Future Directions and Conclusionmentioning
confidence: 99%
“…Finally, in addition to visitation rates, changes due to reduced water availability might also affect pollinator behavior on flowers (Höfer et al, 2021). Behavioral changes, such as increasing handling time, can impact pollen transfer to the stigma and pollen removal and can be better proxies for pollination efficiency than visitation rates (Willcox et al, 2017;Willmer et al, 2017).…”
Section: Caveats Future Directions and Conclusionmentioning
confidence: 99%
“…A meta-analysis from Kuppler and Kotowska (2021) demonstrated consistent decreases in floral size, number of flowers and nectar volume in response to reduced water availability. Although Höfer et al (2021) found that drought did not significantly affect floral volatiles of Sinapis arvensis plants, the mean total scent emission per flower tended to be higher in drought-stressed plants than watered plants. Nutrient stress decreased flower production by Lithophragma bolanderi ( Friberg et al, 2017 ), whereas soil nutrient addition increased floral display size ( Brodbeck et al, 2001 ).…”
Section: Introductionmentioning
confidence: 61%
“…Plant crops under drought stress have reduced photosynthesis and thus decreased growth and produce lower reward and visual cues for pollinators (Descamps et al, 2020 ; Rering et al, 2020 ), affecting the nutritional quality and availability of floral resources for bees and having an impact on their survival (Wilson Rankin et al, 2020 ). Simultaneously, drought can induce changes in floral traits and morphology important for interactions with bumblebees (e.g., number of flowers, size of the flower, petal length and width, and depth of the nectar tube), and flowers might be seen as less attractive to forage on (or difficult to handle if they have a reduced size), affecting the bumblebee behavior and resulting in a reduction in the flower visits, as experimental setups found (Höfer et al, 2021 ; Kuppler et al, 2021 ).…”
Section: Discussionmentioning
confidence: 93%
“…Simultaneously, drought can induce changes in floral traits and morphology important for interactions with bumblebees (e.g., number of flowers, size of the flower, petal length and width, and depth of the nectar tube), and flowers might be seen as less attractive to forage on (or difficult to handle if they have a reduced size), affecting the bumblebee behavior and resulting in a reduction in the flower visits, as experimental setups found (Höfer et al, 2021;Kuppler et al, 2021).…”
Section: Effects Of Mfc and Impacts Of Droughtmentioning
confidence: 99%